Guru agama Kristen Sebagai Teolog Praktika Garis Depan Bagi Siswa - Sostenis Nggebu (Didache: Journal of Christian Education, 2022)
The purpose of this article is to discuss that Christian teachers have an important role in passing on theological concepts to students. This study uses a descriptive method. The result is that Christian teachers become theologians because they carry out their function as teachers in the field of practical theology for students (cf. Eph 4:11-14; Jas 3:1). They are called theologians because the source of their teaching comes from the Scriptures and contributes to the development of a theological framework based on the leading of the Holy Spirit (cf. Jn 14-16). Practically, Christian teachers formulate beliefs or theological arguments that can be used as a reference to build the spiritual life of students so that they know God and love Him through Jesus Christ.